The effect of weight training using Muscle and motion application in some of strength types for boxers - Naser , Abduljaleel; Mohammad, Dham (Journal of Physical Education, 2024)
The aim of the research was to identify the effect of using weight training for the working muscles using muscle and movement applications in some types of strength for boxers., the subject consset of (18) boxers who were divided  into two groups control group and experimental group, the application  consists of two applications: the Anatomy application, which is use for increasing training in exercises and dissecting them, and the Strength Training application, which is an application for strength training. After applying the training exercise for a period of (8) weeks with (3) training units per week, there are statistically significant results between the results of the two groups,